2017
DOI: 10.1371/journal.pone.0179848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anabolic and catabolic nutrients on woody plant encroachment after long-term experimental fertilization in a South African savanna

Abstract: The causes of the worldwide problem of encroachment of woody plants into grassy vegetation are elusive. The effects of soil nutrients on competition between herbaceous and woody plants in various landscapes are particularly poorly understood. A long-term experiment of 60 plots in a South African savanna, comprising annual applications of ammonium sulphate (146–1166 kg ha-1 yr-1) and superphosphate (233–466 kg ha-1 yr-1) over three decades, and subsequent passive protection over another three decades, during wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…However, it might be possible to generalise for alien trees invading Fynbos and Grassland. In particular the shift from a relatively short plant form (shrubs or grasses) to a tall plant form (trees) can be explained in part by the Catabolic Theory (Milewski and Mills 2010;Mills et al 2016Mills et al , 2017. The theory has three main premises: first the availability of catabolic versus anabolic nutrients has marked effects on vegetation structure; second that short plants (e.g.…”
Section: Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it might be possible to generalise for alien trees invading Fynbos and Grassland. In particular the shift from a relatively short plant form (shrubs or grasses) to a tall plant form (trees) can be explained in part by the Catabolic Theory (Milewski and Mills 2010;Mills et al 2016Mills et al , 2017. The theory has three main premises: first the availability of catabolic versus anabolic nutrients has marked effects on vegetation structure; second that short plants (e.g.…”
Section: Soilsmentioning
confidence: 99%
“…The presence or absence of alien trees in fynbos and encroaching native trees in grassland environments of South Africa have been linked to a wide range of nutrients, soil properties, and soil treatments, including pH, acid saturation, Mg, Ca, Mn, Cu, Zn, B, P, and N-fertilisation (Mills and Allen 2018;Mills et al 2017). Unpublished data collected from 25 diverse sites across South African Fynbos, Grassland and Savanna sites have shown that soils in sub-sites relatively poor in boron or relatively rich in phosphorus tend to be less wooded than adjacent sub-sites.…”
Section: Soilsmentioning
confidence: 99%
“…Basal stem diameter measurements were used to calculate basal stem area (πr 2 ) and then summed for each plot to provide a cumulative measure of total woody area (cm 2 ). The methods of soil sampling and analysis are described in Mills et al 7 . All data were analysed using R statistical software.…”
mentioning
confidence: 99%
“…B, Mg and Mn). [13][14][15] The reasoning underpinning the theory is that if a soil nutritional regime favours the production over the metabolism of photosynthates, then a photosynthate surplus arises, which will be used for synthesising wood. The concept of short plants outcompeting tree seedlings is not new 16 , and the Catabolic Theory has been corroborated by studies on treeless vegetation surrounded by treed vegetation in both Australia and South Africa 14,15 .…”
mentioning
confidence: 99%
“…A long-term fertilisation experiment in a South African savanna has shown conclusively that changes in soil nutrient regimes can either promote or entirely constrain woody plant encroachment. 15 It is highly probable that soil nutrients exert similar strong controls on woody plants in all biomes globally, not only in South African savannas. There are 13 plant nutrients which have the potential to affect the competitive interplay between fynbos plants and their woody alien invaders.…”
mentioning
confidence: 99%